The Influence of Price Perception and Perceived Product Quality on Purchase Intention Through Brand Awareness: A Study at Arta Silver Jewelry Store - Arta, Ni Wayan Sinta Kusumayani; Pidada, Ida Ayu Iswari (Economic Reviews Journal, 2025)
The purpose of this study is to examine the effect of Price Perception and Perceived Product Quality on Purchase Intention through Brand Awareness as a mediating variable. The research focuses on consumers initial perceptions of a local jewelry business in Bali. A quantitative approach was employed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results show that Price Perception has a positive but insignificant effect on Purchase Intention, while Perceived Product Quality has a positive and significant effect. Both Price Perception and Perceived Product Quality significantly influence Brand Awareness, and Brand Awareness itself significantly affects Purchase Intention. The mediation analysis reveals that Brand Awareness fully mediates the relationship between Price Perception and Purchase Intention, and partially mediates the relationship between Perceived Product Quality and Purchase Intention. Overall, the findings highlight the crucial role of brand awareness in enhancing purchase intention, particularly for local jewelry businesses that have not yet actively engaged in digital promotion.